STEM Learning dalam Konteks Pendidikan Sains: Analisis Sistematis terhadap Implikasi dan Dampaknya bagi Peserta Didik - Nurbayti, Rini; Novia Arifin, Arifah; Intan Rri Rejeki, Nur; Samad, Hamidah; Adnan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to systematically analyze the implications and impacts of the application of Science, Technology, Engineering, and Mathematics (STEM) in the context of science education on student competencies. The study was conducted through a Systematic Literature Review (SLR) approach to 48 Scopus-indexed scientific articles published in the 2023–2025 period with the keyword STEM Learning and focusing on elementary and secondary education levels. Data analysis was conducted using Microsoft Excel and VOSviewer software to identify publication trends, research focuses, and emerging key themes. The results show that STEM learning has positive implications for strengthening 21st-century competencies, particularly critical thinking, problem-solving, collaboration, and scientific communication skills. In addition, the application of innovative models such as Project-Based Learning, Design Thinking, Co-Learning, STEM-R, and Ethnoscience broadens the meaning of science education to be more contextual and humanistic. STEM learning also emphasizes the strategic role of teachers as facilitators of innovation and agents of educational change. Overall, this study concludes that STEM implementation is an effective strategy for comprehensively developing students' scientific literacy and character, while also providing direction for developing a science curriculum relevant to 21st-century needs.